Urinary excretion of platinum (Pt) following skin and respiratory exposure to soluble Pt at South African precious metals refineries - Linde, Stephanus J.L.; Franken, Anja; du Plessis, Johannes L. (International journal of hygiene and environmental health, 2018)
[Display omitted] •This is the first study to report occupational skin exposure to soluble Pt.•This is the first study to correlate occupational skin and respiratory exposure to soluble Pt with urinary Pt excretion.•Partial correlations revealed significant positive correlations between skin and respiratory exposure and urinary Pt excretion.•Differences in work areas primarily influenced workers’ skin and respiratory exposure and their urinary Pt excretion.•Skin exposure can possibly lead to the uptake of minor concentrations of Pt and increased urinary Pt excretion. Adverse respiratory and skin health effects have been associated with occupational exposure to soluble platinum (Pt). However, the relationship between skin exposure and urinary Pt excretion has not yet been investigated. In this study we examined the relationship between skin and respiratory exposure to soluble Pt and urinary Pt excretion at two South African precious metals refineries. The skin and respiratory exposure to soluble Pt as well as the urinary Pt excretion of forty precious metals refinery workers was assessed simultaneously using Ghostwipes™, Methods for the Determination of Hazardous Substances method 46/2 and spot urine tests, respectively. The geometric mean for skin exposure to soluble Pt on four anatomical positions (palm, wrist, neck and forehead) was 0.008 μg/cm2 [95% confidence interval (CI): 0.005-0.013 μg/cm2], while the geometric mean for respiratory exposure was 0.301 μg/m3 (95%CI: 0.151-0.601 μg/m3) and the geometric mean for urinary Pt excretion was 0.212 μg/g creatinine (95%CI: 0.169-0.265 μg/g creatinine). Partial correlations identified significant positive correlations between skin exposure, respiratory exposure and urinary Pt excretion (r = 0.580 to 0.754). Skin and respiratory exposures to soluble Pt were both positively correlated with urinary Pt excretion, and both exposure routes should be considered when investigating occupational exposure to soluble Pt.